Lactobacillus casei 64H Contains a Phosphoenolpyruvate-Dependent Phosphotransferase System for Uptake of Galactose, as Confirmed by Analysis of ptsH and Different gal Mutants - Bettenbrock, Katja (American Society for Microbiology (ASM), 1999)
Galactose metabolism in Lactobacillus casei 64H was analyzed by genetic and biochemical methods. Mutants with defects in ptsH, galK, or the tagatose 6-phosphate pathway were isolated either by positive selection using 2-deoxyglucose or 2-deoxygalactose or by an enrichment procedure with streptozotocin. ptsH mutations abolish growth on lactose, cellobiose, N-acetylglucosamine, mannose, fructose, mannitol, glucitol, and ribitol, while growth on galactose continues at a reduced rate. Growth on galactose is also reduced, but not abolished, in galK mutants. A mutation in galK in combination with a mutation in the tagatose 6-phosphate pathway results in sensitivity to galactose and lactose, while a galK mutation in combination with a mutation in ptsH completely abolishes galactose metabolism. Transport assays, in vitro phosphorylation assays, and thin-layer chromatography of intermediates of galactose metabolism also indicate the functioning of a permease/Leloir pathway and a phosphoenolpyruvate-dependent phosphotransferase system (PTS)/tagatose 6-phosphate pathway. The galactose-PTS is induced by growth on either galactose or lactose, but the induction kinetics for the two substrates are different.